Stakeholders analysis of COVID-19 management and control: a case of Iran - Mohammad Mohamadian; Taha Nasiri; Mohammadkarim Bahadori; Habib Jalilian (BMC, 2022)
Abstract Background The COVID-19 pandemic is a multi-faceted phenomenon with many political, economic and social consequences. Success in managing and controlling this pandemic depends on the coordinated efforts of many organizations and institutions. Therefore, this study aimed to identify and analyze the actors and stakeholders related to managing and controlling this pandemic in Iran. Methods This mix-method stakeholder analysis was conducted in 2021 nationwide as retrospectively. The purposive sampling method was applied when inviting eligible participants to participate in the study. Our study was conducted in two phases. In the qualitative phase, data were collected using a semi-structured interview. An interview guide was developed based on the WHO stakeholder analysis framework. In the quantitative phase, we used a questionnaire developed based on the study framework. Each question was scored on a 5-point Likert scale, with a score greater than 4 was considered as high, 3-4 was considered as moderate, and 1-3 was considered as low. Data were analyzed using framework analysis, WHO stakeholders' analysis framework and MENDELOW matrix. MAXQDA qualitative data analysis software Version 11 and Policy Maker software (Version. 4) were used for data analysis. Results A total of 48 stakeholders were identified. Ministry of Health (MoH), National Headquarters for Coronavirus Control (NHCC) had the highest participation level, high supportive position, and knowledge of the subject. The Parliament of Iran (PoI), Islamic Revolutionary Guard Corps (IRGC), and Islamic Republic of Iran Broadcasting (IRIB) had the highest power/influence during the Covid-19 epidemic. Only two stakeholders (6.06%) had high participation, and 18.18% had moderate participation. All stakeholders except for the NHCC and the MoH lacked appropriate knowledge of the subject. Furthermore, only three stakeholders (9.09%) had high power/influence. Conclusion Given the multidimensional nature of Covid-19, most institutions and organizations were involved in managing this pandemic. Stakeholders with high power/authority and resources had a low/moderate participation level and a moderate supportive position. Moreover, organizations with a high supportive position and participation had low power/authority and resources to cope with COVID-19.